Physician Perceptions of Performance Feedback in a Quality Improvement Activity. (May 2018) - Eden, Aimee R.; Hansen, Elizabeth; Hagen, Michael D.; Peterson, Lars E.
Physician performance and peer comparison feedback can affect physician care quality and patient outcomes. This study aimed to understand family physician perspectives of the value of performance feedback in quality improvement (QI) activities. This study analyzed American Board of Family Medicine open-ended survey data collected between 2004 and 2014 from physicians who completed a QI module that provided pre- and post-QI project individual performance data and peer comparisons. Physicians made 3480 comments in response to a question about this performance feedback, which were generally positive in nature (86%). Main themes that emerged were importance of accurate feedback data, enhanced detail in the content of feedback, and ability to customize peer comparison groups to compare performance to peers with similar patient populations or practice characteristics. Meaningful and tailored performance feedback may be an important tool for physicians to improve their care quality and should be considered an integral part of QI project design.